Teaching English Vocabulary to Young Learners with Wordwall Application: An Experimental Study - Pradini, Putu Cening; Adnyayanti, Ni Luh Putu Era (Journal of Educational Study, 2022)
The pandemic period changed the education system in Indonesia. Online learning has been implemented since 2020, and face-to-face learning will gradually begin in 2021. As online learning is implemented, various learning media have been used by teachers to help students understand the material content during online learning. However, the lack of student motivation during online learning becomes the main problem. Especially for young students who find it difficult to concentrate while studying. Teachers need learning media that are more creative and attract students' attention and motivation to learn. Vocabulary is one of the basic components of English that have to be mastered by students. Therefore, this research specifically aimed to improve the English vocabulary of young learner students at SDN 1 Mambang by using Wordwall. The material given includes three vocabulary components: nouns, verbs, and adjectives. This research study is a one-shot case study that will use one participant to be given treatment. This study aimed to see the improvement or achievement of young learner students' vocabulary by using a word wall. This research is a quantitative study. The data obtained from the pre-test and post-test will be presented quantitatively. This study shows that the mean score of the student in the pre-test was 53.33, categorized as satisfactory, and the student's scores in the post-test increased by 73.33, categorized as good. After receiving treatment, the total percentage of students' vocabulary achievement development was 37.50%. This shows that word wall can increase students' vocabulary achievement and motivation to learn English.